Predictive Analysis of Hip-hop Dancers’ Motivation for Choreographing from Choreography Components (Body-Thinking-Space-Time) - Vivi Angelina; Juneman Abraham (ANIMA Indonesian Psychological Journal, 2015)
This study aimed to examine several variables to predict motivation in creating dance choreography, i.e. sense of embodiment, integrative thinking, object and spatial imagery, as well as two types of time perspective (Present Hedonistic and Future). The participants of this study were 34 female Hip-hop dancers and 31 male Hip-hop dancers (n = 65, Mage = 21.08 years old, SDage = 1.674 years old) in Jakarta, the capital city of Indonesia, recruited via convenience sampling. Data were obtained through psychological scales and were analyzed using a multiple linear regression analysis. Results showedthat (1) the adaptive behavior dimension of motivation could be predicted from the sense of embodiment, object and spatial imagery, and time perspective of future and present hedonistic; (2) the adaptive cognition dimension could be predicted from the object and spatial imagery; (3) the maladaptive behavior dimension could be predicted from the object and spatial imagery and present hedonistic time perspective; and (4) the maladaptive cognition dimension could be predicted from integrative thinking, spatial imagery, and present hedonistic time perspective.